Automated Control System of 35 KV and Higher Power Networks - M. I. Fursanov; A. A. Zalatoi; A. N. Mukha; V. I. Privalov; I. V. Krupa (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
The paper contains description of an automated control system of 35 kV and higher power networks, developed by the BNTU in collaboration with research-and-production firm «Dipol» and introduced at «Minskenergo» power networks. The description of algorithms for solution of some technological problems realized in the library of applied programs that presents a calculative nucleus of the given developed system. Connection procedure of the developed applied program library to the operative and measuring complex of the automated system is given in the paper.